Climate Security Observatory – SENEGAL. Summary for Policymakers - CGIAR FOCUS Climate Security (CGIAR FOCUS Climate Security, 2022)
Senegal has far fewer conflicts than any other country in the Sahel and is considered one of the most stable countries in Africa. However, the south of the country is the scene of the longest-running armed conflict in Africa between the government and separatist groups in Casamance. Although it has evolved since the early 2000s into a low-intensity war that does not pose a significant security threat, it is still a source of instability in certain areas of the south of the country, where rebels control illegal logging and timber trade. While the conflict is primarily related to lower socioeconomic development and resentment of the central government, which has exacerbated feelings of marginalization and increased separatist sentiment, deteriorating climatic conditions and the increasing number of extreme weather events may negatively affect conflict and security dynamics in the country through their impact on natural resource availability and livelihoods. This profile, derived from the Climate Security Observatory, answers: 1) HOW does climate worsen the root causes of conflict? 2) WHERE are the most vulnerable areas to climate induced insecurities and risks? 3) WHO are the vulnerable groups to climate and security risks that should be targeted? and 4) WHAT needs to be done to break the cycle between climate and conflict?